The Social Construction of Transgenic Corn: Relevant Social Actors in Chihuahua - Marco Antonio Fernández Nava (Íconos)
According to the socio-technical perspective, the meaning of a technological artefact does not lie within the artefact itself. Analyzing transgenic corn from a socio-technical perspective means taking one’s research beyond the artefact itself. To do this, it is necessary to overcome and avoid determinist positions, be they social or technological. This work takes as it point of departure the Social Construction of Technology Focus (SCOT). In this sense, transgenic corn is an unfinished object that is affected by an onslaught of struggles, opinions, agreements, disagreements, designs and redefinitions of the relevant social actors. These groups, the Democratic Campesino Front, El Barzón, National Agro-dynamic and Regional Agricultural Union of Yellow Corn Producers (UNIPRO), demonstrate how technological development is a social process. The deconstruction of transgenic corn according to the perspectives of these different social actors is key to the process of constructivist analysis: to take the artefacts just as each social actor views them. The objective of this study then is to describe how the different social groups, through their actions, construct and deconstruct the meaning of transgenic corn in Chihuahua, Mexico.